2016
DOI: 10.1002/jmri.25512
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of three‐dimensional late enhancement MRI

Abstract: 2 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2017;45:1675-1683.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…The in‐plane resolution of the 2D scan was higher than the 3D; in our study the 2D scan was clinically optimized and established and we wanted to directly compare with it; the 3D scan was separately optimized, balancing resolution and acceleration. Typically, 3D LGE techniques have been shown to have compromised image quality compared with 2D techniques, although differences in qualitative ratings often do not reach significance . Our findings were that categorical image scoring of the 3D mDIXON sequence was in fact very comparable to the 2D LGE sequence.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The in‐plane resolution of the 2D scan was higher than the 3D; in our study the 2D scan was clinically optimized and established and we wanted to directly compare with it; the 3D scan was separately optimized, balancing resolution and acceleration. Typically, 3D LGE techniques have been shown to have compromised image quality compared with 2D techniques, although differences in qualitative ratings often do not reach significance . Our findings were that categorical image scoring of the 3D mDIXON sequence was in fact very comparable to the 2D LGE sequence.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, accurate discrimination of transmural scar extent is important when considering a new LGE sequence. Previous studies have showed variable results, although more recent studies have shown reasonable agreement . The 3D mDIXON technique showed strong agreement with the 2D sequences.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…These navigated sequences may enable the assessment of thin walled structures such as atria and RV free wall although acquisition durations are long (typically 5–10 min) and unpredictable (69). …”
Section: Focal Fibrosis and Scarringmentioning
confidence: 99%
“…While adenosine stress imaging assesses myocardial perfusion, late gadolinium enhancement (LGE) depicts myocardial scar . Recently introduced 3D acquisition sequences make use of 3D excitation and readout of the entire examination volume at once instead of repeatedly acquiring separate slices . For perfusion imaging, such 3D sequences proved diagnostic accuracy at higher spatial resolutions .…”
mentioning
confidence: 99%